The analysis of molten salt energy storage mode with multi-steam sources heating in thermal power unit peak shaving operation - Lin-kui Feng; Yao-fei Feng; Ke Lu; Ping Wang; Kai Zhao; Zhi-de Gu; Yan-nan Ren; Sheng-lu Xie (Scientific Reports)
Abstract A 350 MW cogeneration unit was selected as the research object to investigate a molten salt energy storage system. Key evaluation indicators, including peak shaving capacity, thermal efficiency, equivalent round-trip efficiency, and comprehensive coal consumption, were analyzed under heat storage-release strategies involving single-steam source and multi-steam source heating, combined with steam grade and steam split ratio. The thermoelectric characteristic curve of the unit during the heat storage-release phase was determined based on the storage-release characteristics of the molten salt system. The results indicate that under heat storage mode, similar peak shaving depths are achieved with both single-steam source and multi-steam source heating strategies. However, thermal efficiency is higher with the multi-steam source strategy, and peak shaving capacity improves with an increased steam split ratio. During heat release mode, higher peak shaving capacity is achieved when steam is matched with the grade of cold reheat steam.